The sexual assault against children in UAE society: A qualitative sociological study about after the sexual assault stage and the reflection on it - Humaid, Helema Mohammed; Al-Hourani, Mohammed (Al-Adab Journal, 2022)
This scientific paper studies sexual abuse against children in the UAE community, as it highlights the current state of the victim in terms of mental, social and educational aspects, in addition to the continuity of receiving psychological and social care and how stable the victims' situation is. The study also focuses on the victims' reflection and contemplation of the past in terms of the person who’s blamed for the incident, how sufficient were their actions following the incident, and if time goes back what could’ve been done differently, and any advice given to others on this matter. The study sample consisted of 28 victims from child protection centers in Dubai and Sharjah. Results show that the effects of sexual assault vary within victims in terms of psychological, social and educational aspects. In addition to the varying opinions of the victims and their families, and their reflection on the sexual assault.